GENERAL ISSUES OF THE METHODOLOGY OF TEACHING PHYSICS. - Absalyamova Ilmira Ildarovna; Karimova Nozliya Nabijon kizi (Ta’lim innovatsiyasi va integratsiyasi, 2023)
Annotation: This article delves into the general issues surrounding the methodology of teaching physics, exploring the challenges and opportunities in this dynamic field of education. Through a thorough literature analysis, the article examines existing approaches, evaluates their effectiveness, and proposes innovative methods to enhance the teaching and learning experience in physics classrooms. The methods section outlines practical strategies, while the results and discussion sections critically assess their impact. The article concludes with key takeaways and suggestions for educators to implement in their physics instruction.